An approach oriented viewpoints for cooperative information system eliciting requirements. (9th October 2019) - Kessi, Kahina; Alimazighi, Zaia; Oussalah, Mourad Chabane
Cooperative information system (CIS) is a complex system that involves the cooperation of several stakeholders sharing a common purpose, with different viewpoint on the system. This makes its development more difficult. The successful design of a CIS is then mainly based on the definition of the requirements engineering phase. In software engineering domain, especially in requirements engineering domain, Viewpoint and abstraction level are two important concepts introduced to reduce systems complexity. In this paper, we present an approach oriented viewpoints/abstraction levels which defines the necessary concepts to elicit the requirements of a CIS. In doing so, a model driven method is proposed to develop a CIS modelling tool. In this method, we proposed first a meta-model oriented viewpoints/abstraction levels which decomposes a CIS according to its different viewpoints. We then proposed a modelling tool, viewpoints for cooperative information system (VpCIS) generated from the meta-model.